2000
DOI: 10.1038/sj.bmt.1702576
|View full text |Cite
|
Sign up to set email alerts
|

Successful bone marrow transplantation in a child with red blood cell pyruvate kinase deficiency

Abstract: Summary:We report the first successful use of BMT for the treatment of RBC pyruvate kinase (PK) deficiency in a boy who developed neonatal jaundice and severe transfusion-dependent hemolytic anemia a few months after birth. He received a BMT at the age of 5 from an HLAidentical sister who has normal PK activity after conditioning with busulfan and cyclophosphamide. The post-transplant course was uneventful. At present, 3 years after transplant, he is 8 years old and has a normal hemoglobin level and normal RBC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 8 publications
1
35
0
2
Order By: Relevance
“…Splenectomy can be clinically useful in patients with severe disease, and in some cases allogeneic hematopoietic transplantation is required (Suvatte et al, 1998;Tanphaichitr et al, 2000). In these patients, hematopoietic stem cell gene therapy could be an effective, less invasive alternative.…”
Section: Introduction P Yruvate Kinase Deficiency (Pkd) Is An Autosommentioning
confidence: 98%
“…Splenectomy can be clinically useful in patients with severe disease, and in some cases allogeneic hematopoietic transplantation is required (Suvatte et al, 1998;Tanphaichitr et al, 2000). In these patients, hematopoietic stem cell gene therapy could be an effective, less invasive alternative.…”
Section: Introduction P Yruvate Kinase Deficiency (Pkd) Is An Autosommentioning
confidence: 98%
“…4,5 To date, only four human cases of HSCT have been published in the literature. [6][7][8] The total number of cases transplanted worldwide is unknown.…”
mentioning
confidence: 99%
“…HSCT has been used in animal models, 13,16,17 and a case of successful bone marrow transplantation has been reported recently. 15 Non-myeloablative HSCT seems a favorable strategy for the treatment of PK deficiency, as indicated in animal model studies, since erythroid progenitors with normal R-PK show a selective growth advantage. 13,17 Enzyme-replacement therapy is another candidate for causative-targeted therapy of severe hemolytic anemia due to RBC enzyme defects.…”
Section: Discussionmentioning
confidence: 99%
“…Although hematopoietic stem cell transplantation (HSCT) has been considered as a therapeutic strategy for PK deficiency in a PK-deficient subject 15 as well as in animal models, 13,16,17 a curative therapy without any lifethreatening complications needs to be developed. In addition, the majority of the identified PK gene mutations are missense mutations, 2,3 and previous studies revealed that there were some kinetically aberrant enzymes, which showed normal intracellular stability in erythroid cells.…”
mentioning
confidence: 99%